Polling in the frequency domain: a new MAC protocol for industrial wireless network for factory automation. (2015) - Lin, Junru; Liang, Wei; Yu, Haibin; Xiao, Yang
Wireless technologies are becoming more and more attractive for industrial communication. In the field of factory automation, the high communication requirements in terms of predictability, reliability and real-time make the adoption of wireless technologies challenging, due to the inefficiency of the wireless physical layer and deterministic medium access control (MAC) protocols. In this paper, a frequency domain polling MAC protocol (FDP-MAC) is proposed, which takes advantage of the orthogonal frequency-division multiplexing (OFDM) technology to achieve simultaneously polling. In the FDP-MAC, a dynamic time division multiple access (TDMA) scheduling and a downlink acknowledgements aggregation method are also presented to improve the communication efficiency further. We validate the effectiveness of FDP-MAC through simulations, and results indicate that FDP-MAC can meet typical factory automation applications' communication requirements.